2006
DOI: 10.1074/jbc.m510803200
|View full text |Cite
|
Sign up to set email alerts
|

Repletion of Atypical Protein Kinase C following RNA Interference-mediated Depletion Restores Insulin-stimulated Glucose Transport

Abstract: The role of atypical protein kinase C (aPKC) in insulin-stimulated glucose transport in myocytes and adipocytes is controversial. Whereas studies involving the use of adenovirally mediated expression of kinase-inactive aPKC in L6 myocytes and 3T3/L1 and human adipocytes, and data from knock-out of aPKC in adipocytes derived from mouse embryonic stem cells and subsequently derived adipocytes, suggest that aPKCs are required for insulin-stimulated glucose transport, recent findings in studies of aPKC knockdown b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…able to offer a satisfactory explanation for this discrepancy in results but can only support suggestions put forward previously to explain similar discrepancies (31), namely that variations in the introduction of small-interfering RNA/shRNA in the cells may have an impact on the results observed. Our reported levels of RNAi-mediated knockdown at both mRNA and protein levels are similar to that reported in other studies, so it is unlikely that differing levels of knockdown are at the root of the different responses observed.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…able to offer a satisfactory explanation for this discrepancy in results but can only support suggestions put forward previously to explain similar discrepancies (31), namely that variations in the introduction of small-interfering RNA/shRNA in the cells may have an impact on the results observed. Our reported levels of RNAi-mediated knockdown at both mRNA and protein levels are similar to that reported in other studies, so it is unlikely that differing levels of knockdown are at the root of the different responses observed.…”
Section: Discussioncontrasting
confidence: 40%
“…Studies using RNAi techniques in 3T3-L1 adipocytes have suggested that depletion of aPKC has no discernible effects on insulin-stimulated glucose uptake (43), whereas other groups have demonstrated that a similar depletion results in loss of insulin-stimulated glucose uptake (31). Currently, we are un- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that FAK differentially regulates insulin signalling under normal and insulinresistant conditions. Sajan et al [39] recently reported a differential role of the atypical PKC isoforms ζ and λ in insulin-stimulated glucose transport. Regulation of GLUT4 translocation in skeletal muscle of high-fat-diet-fed rats by PKC (ζ/λ) has also been reported [40].…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of JNK a significant number of IRS kinases are also required for insulin-dependent metabolic control. For example, ERK1/2 are believed to link insulin with cell proliferation, differentiation and the regulation of lipid metabolism, glycogen synthase kinase (GSK)-3 is required to regulate glycogen stores in muscle and liver, S6K to control protein synthesis, and isoforms of PKC may be required for insulin-induced glucose transport (Avruch, 1998;Bandyopadhyay et al, 2000;Bandyopadhyay et al, 2002;Copps et al, 2010;Kotzka et al, 2004;Martin and Parton, 2006;Roth et al, 2000;Ryden et al, 2004;Sajan et al, 2006).…”
Section: Irs Proteins and The Development Of Insulin Resistancementioning
confidence: 99%